(untitled) (Papeles, 2022)
Introduction: The objective of this study was to develop a training program on inclusive education for high school teachers. Methodology: For this purpose, a quantitative approach methodology was used, with a transversal design based on descriptive and exploratory research. The sample consisted of 30 male and female teachers. The data collection instrument was the questionnaire validated by the criteria of experts, supported by the survey technique. A data analysis based on descriptive statistics techniques was presented. Results and discussion: The first result was that there was a considerable and acceptable level of training on inclusive education on the part of the teachers. The second result was the design and implementation of a training program for teachers on inclusive education, which helped to create a harmonious and enriching training climate. The third result was that after the application of the training program on inclusive education, there was satisfaction on the part of the teachers, both in terms of mood and academics. Conclusions: In short, it is shown that there were favorable results thanks to the intervention proposal, demonstrating that a training program contributes to teacher training on inclusive education.